Coral Reef and Shallow Water Benthic Identification Using Landsat 7 ETM+ Satellite Data in Nusa Penida District - Arief Reza Fahlevi; Takahiro Osawa; I Wayan Arthana (Graduate Study of Environmental Sciences, Postgraduate Program of Udayana University, 2018)
This study aims to investigate the feasibility of Landsat 7 ETM+ to identify coral reefs and shallow water benthic at Nusa Penida district in 2009 and 2012, comparison with the Reef Health Monitoring (RHM) results conducted by the Coral Triangle Center (CTC) using the Point Intercept Transect (PIT) method in the same periods. This study also aims to determine the changes of coral reefs and shallow water benthic cover during this period and the distribution at Nusa Penida districk. Shallow water benthic classification refers to English et al. (1997), with a modified by the addition of vegetation classes (seagrass and seaweed). The classification result using confusion matrix between the Reef Health Monitoring (RHM) with the classification of satellite image in 2009 obtained an accuracy rate of 65.85% with a kappa coefficient value of 0.525, while in 2012 the accuracy value obtained of 74.81% with kappa coefficient value of 0.650, which shows the results of that classification of satellite images of Landsat 7 ETM+ with the results of in-situ research is in a moderate level.